The complete Peanuts, 1961 to 1962 - Schulz, Charles M. (Charles Monroe), 1922-2000. (New York : Distributed to the book trade by W.W. Norton, 2006)
Collects Charles Schulz's daily and Sunday "Peanuts" strips from 1961 and 1962, which chronicle the adventures of Charlie Brown, Snoopy, and friends.
Includes index.
Booklist.
Booklist, November 2006.
Young Adult
Keywords: Brown, Charlie (Fictitious character) -- Fiction; Children -- Fiction; Snoopy (Fictitious character) -- Fiction; Brown, Charlie (Fictional character) -- Fiction; Children -- Fiction; Comic books, strips, etc; Snoopy (Fictional character) -- Fiction